Scutellarin combined with lidocaine exerts antineoplastic effect in human glioma associated with repression of epidermal growth factor receptor signaling. - Xiu-Ying He; Yui-Si Yang; Yue-Xiang Zheng; Qing-Jie Xia; Hong-Zhou Yu; Xiao-Ming Zhao; Ting-Hua Wang (PLoS ONE)
Purpose Glioma is the most common primary intracranial tumors. Although great achievements have been made in the treatment, the efficacy is still unsatisfactory, which imposes a hefty burden on patients and society. Therefore, the exploration of new and effective anti-glioma drugs is urgent. Methods Human glioma cell lines U251 and LN229 were included in the study. Cell proliferation was detected by cell counting kit-8 (CCK8), plate clone formation assay, EdU incorporation assay and xCELLigence real-time cell analyzer. Cell apoptosis was evaluated by TUNEL assay and flow cytometry. Then, transwell assay was used for assessing the migration. Moreover, tumor xenograft model was established to examine the effect of scutellarin (SCU) and lidocaine on the growth of glioma in vivo. Lastly, western blot was performed to detect the protein level of epidermal growth factor receptor (EGFR). Results In present study, we found that SCU and lidocaine suppressed the proliferation and migration, and induced the apoptosis of human glioma cell lines, including U251 and LN229 cells, in a dose-dependent manner in vitro. Moreover, the combination of SCU and lidocaine further restrained the proliferation and migration ability of U251 and LN229 cells, while induced their apoptosis in vitro. Additionally, SCU and lidocaine also inhibited the growth of glioma in vivo, and the effect of the combination was better. Above all, the toxicity of SCU and its combination with lidocaine was low to normal astrocytes and neurons. Mechanistically, the effect of SCU and its combination with lidocaine on glioma cells was partially associated with the repression of EGFR signaling. Conclusions Scutellarin and lidocaine exerted a synergistic effect on suppressing the proliferation and migration and inducing the apoptosis of glioma cells, which was partly associated with the repression of EGFR signaling.